Development Strategy for Environmental Education–Based Ecotourism Programs Using Gap Analysis and Importance–Performance Analysis - Occy Bonanza; Melewanto Patabang; Kania Sofiantina Rahayu; Dyah Prabandari; Leni Lidya (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study aims to evaluate and develop environmental education–based ecotourism programs to enhance visitor satisfaction and destination sustainability. Methods: The study employed a quantitative approach involving 100 respondents selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using GAP analysis, paired sample t-test, and Importance–Performance Analysis (IPA). Results: The findings indicate that Godong Ijo offers 25 tourism programs, with most attributes showing positive GAP values, suggesting that program performance has met visitor expectations. However, three attributes exhibited negative GAP values, with Fishing Competition having the lowest score (-0.12), followed by Junior Master Chef (-0.03) and Aero Glider (-0.02), indicating the need for improvement. The t-test results revealed a significant difference between the importance and performance levels of the tourism programs (p = 0.000), indicating a gap between visitor expectations and their actual experiences. The IPA results show that five attributes—Junior Master Chef, Fun with Clay, Eco-Science Robo-Art Class, Fishing Competition, and Vertical Garden—fall into the main priority quadrant, meaning they are considered highly important but their performance remains suboptimal. Contribution: This study confirms that the integration of GAP analysis and IPA is effective in identifying priorities for tourism program development in a more targeted manner. The findings are expected to serve as a basis for formulating more adaptive, sustainable, and experience-oriented ecotourism management strategies.